The effect of a positive result of Covid PCR test in an asymptomatic pregnant mother on the weight and Apgar score of infants after birth - Fatemeh Khalighi; Fariba Fahami; Masoume Pirhadi (Mashhad University of Medical Sciences, 2023)
Introduction: The lack of information about the impact of Covid-19 on pregnancy and the increased side-effects of the disease for pregnant mothers and fetuses showed the importance of investigating its impact on pregnancy and neonate. The present study was performed with aim to investigate the impact of positive test result of PCR on the weight and Apgar scores of infants. Methods: In this analytical study (retrospective cohort), sampling was conducted by examining the files of 98 pregnant women who gave birth between April 2020 and September 2021 using the apple system which were covered by health care centers located in Isfahan province. The information obtained from the comparison of two groups of mothers based on the results of the PCR test was analyzed by SPSS software (version 18) and Independent t-test. P<0.05 was considered statistically significant. Results: Among the examined files, 50 cases (51%) had a positive PCR test and 48 cases (49%) had a negative PCR test. 99% of the infants had an Apgar score of ≥7. According to the results of Independent t-test, no significant difference was found between the Apgar score at minute 1 (p=0.714) and minute 5 (p=0.580) of the infants of PCR+ and PCR- mothers. Also, According to the results of Independent t-test, no significant difference was found between the weight of newborns in mothers of two groups (p=0.112). Conclusion: The positive PCR test result has no significant relationship with the weight and the Apgar-score of the 1st and 5th minute of the newborn. Research on the effects of COVID-19 infection during pregnancy continues to be completed and updated. Further research with more samples can better show the possible complications of this disease.